Hid from our eyes [compact disc, unabridged] - Spencer-Fleming, Julia (A Clare Fergusson/Rus Van Alstyne mystery, 2020)
1952. Millers Kill Police Chief Harry McNeil is called to a crime scene where a woman in a party dress has been murdered with no obvious cause of death. 1972. Millers Kill Police Chief Jack Liddle is called to a murder scene of a woman that's very similar to one he worked as a trooper in the '50s. The only difference is this time, they have a suspect. Young Vietnam War veteran Russ van Alstyne found the body while riding his motorcycle and is quickly pegged as the prime focus of the investigation. Present-day. Millers Kill Police Chief Russ van Alstyne gets a 911 call that a young woman has been found dead in a party dress, the same MO as the crime he was accused of in the '70s. The pressure is on for Russ to solve the murder before he's removed from the case.